2012
DOI: 10.1002/pssa.201228277
|View full text |Cite
|
Sign up to set email alerts
|

Role of hot carriers in the interfacial transport in amorphous silicon/crystalline silicon heterostructure solar cells

Abstract: The transport of photogenerated minority carriers (photocarriers) across the heterointerface of amorphous silicon (a‐Si) and crystalline silicon (c‐Si) in a‐Si/c‐Si heterostructure solar cell is shown in this work to critically depend on the non‐Maxwellian energy distribution function (EDF) of those carriers impinging on the heterointerface. A theoretical model is presented that integrates the effect of the high electric field inversion region upon EDF of the impinging carriers with the transmission probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Indeed, several experimental reports (e.g., [16]- [19]) have suggested a link between the properties of a-Si and the occurrence of a nonideal "S-type" curve under certain circumstances. Furthermore, numerical modeling was used to understand the transport mechanism under light, using tunneling across the a-Si/c-Si interface and drift-diffusionbased transport [20], as well as hot-carrier-based transport [21]. These studies were mainly confined to understanding the light I-V properties, with no specific effort to correlate the features to the dark I-V.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several experimental reports (e.g., [16]- [19]) have suggested a link between the properties of a-Si and the occurrence of a nonideal "S-type" curve under certain circumstances. Furthermore, numerical modeling was used to understand the transport mechanism under light, using tunneling across the a-Si/c-Si interface and drift-diffusionbased transport [20], as well as hot-carrier-based transport [21]. These studies were mainly confined to understanding the light I-V properties, with no specific effort to correlate the features to the dark I-V.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic decay energy is traditionally found to be 45 meV in literature (see Ref. [4]). But by varying the decay energy from 5 meV-100 meV it is possible to generate defect densities of 10 18 cm -3 to 10 20 cm -3 .…”
Section: Alternate Defect Distributionsmentioning
confidence: 99%
“…1) together create an unconventional situation where assumptions made by the conventional drift diffusion model are no longer valid. Previous work by Ghosh et al [4] has shown the effect of high fields on the carrier distribution at the heterointerface. In this work we explore and study the various mechanisms that govern transport of photogenerated carriers in the intrinsic amorphous silicon barrier.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, Ghosh et al [53] used ensemble Monte Carlo (EMC) simulations to investigate the effect of high electric fields on photogenerated holes at the a-Si:H(i)/c-Si heterointerface using a single band model. In this chapter, an in-house EMC solver is presented which extends the EMC approach developed by Ghosh et al to model high field effects.…”
Section: Ensemble Monte Carlomentioning
confidence: 99%